2022
DOI: 10.1136/bmjopen-2021-055396
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-related risk perceptions, social influences and public smoke-free policies in relation to smoke-free home restrictions: findings from a baseline cross-sectional survey of Armenian and Georgian adults in a community randomised trial

Abstract: ObjectivesGiven high prevalence of smoking and secondhand smoke exposure in Armenia and Georgia and quicker implementation of tobacco legislation in Georgia versus Armenia, we examined correlates of having no/partial versus complete smoke-free home (SFH) restrictions across countries, particularly smoking characteristics, risk perceptions, social influences and public smoking restrictions.DesignCross-sectional survey study design.Setting28 communities in Armenia and Georgia surveyed in 2018.Participants1456 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“… 15 , 16 Moreover, SHSe rates in Armenia and Georgia are concerning—with estimates of past-month SHSe of 74.2% (79.5% in Armenia, 68.9% in Georgia) and daily SHSe of 24.4%—and SHSe rates are high even where smoking is prohibited. 17 , 18 Although Armenia and Georgia ratified the FCTC in 2004 and 2006, respectively, progress in advancing tobacco control, including smoke-free policy, has lagged. However, both countries have made substantial advances in implementing public smoke-free policies, effective in Georgia since 2018 and in Armenia since 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 Moreover, SHSe rates in Armenia and Georgia are concerning—with estimates of past-month SHSe of 74.2% (79.5% in Armenia, 68.9% in Georgia) and daily SHSe of 24.4%—and SHSe rates are high even where smoking is prohibited. 17 , 18 Although Armenia and Georgia ratified the FCTC in 2004 and 2006, respectively, progress in advancing tobacco control, including smoke-free policy, has lagged. However, both countries have made substantial advances in implementing public smoke-free policies, effective in Georgia since 2018 and in Armenia since 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this progress, 2018 data indicated that smoking is allowed in >75% of homes in Armenia and ∼50% of homes in Georgia. 18 With the recent implementation of national smoke-free policies, understanding theoretical factors (e.g. outcome expectancies, perceived barriers) related to implementing SFHs is crucial for deterring potential displacement of smoking behaviors to private settings and capitalizing on a critical period for promoting SFHs.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking rates among men are among the top ten highest globally (56.1% and 49.5%, respectively); rates among women are lower (2.6% and 8.5%) 34 35. Moreover, 74.2% of people (79.5% in Armenia, 68.9% in Georgia) experience past-month SHSe, with 24.4% experiencing daily SHSe 36. SHSe rates are high even where smoking is prohibited 36 37.…”
Section: Introductionmentioning
confidence: 99%
“… 34 35 Moreover, 74.2% of people (79.5% in Armenia, 68.9% in Georgia) experience past-month SHSe, with 24.4% experiencing daily SHSe. 36 SHSe rates are high even where smoking is prohibited. 36 37 Armenia and Georgia ratified the FCTC in 2004 and 2006, respectively; yet, tobacco control progress has lagged until recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation